2003
DOI: 10.1016/j.amjgastroenterol.2003.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Gastric acid control with esomeprazole, lansoprazole, omeprazole, pantoprazole, and rabeprazole: a five-way crossover study

Abstract: Esomeprazole at the standard dose of 40 mg once daily provided more effective control of gastric acid at steady state than standard doses of lansoprazole, omeprazole, pantoprazole, and rabeprazole in patients with symptoms of gastroesophageal reflux disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(151 citation statements)
references
References 0 publications
9
138
2
2
Order By: Relevance
“…A more favorable metabolism of esomeprazole leads to an increase in plasma AUC (esomeprazole, 20 mg/day, shows an AUC which is almost doubled compared to omeprazole at the same dosage) [62], which in turn corresponds to increased amounts of the drug reaching the pumps in the gastric parietal cells. Indeed, esomeprazole 20 mg/day exerts a superior intragastric pH control (pH ≥4) compared to the same dose of omeprazole at 8, 12, and 16 h in patients with GERD [59]. As a consequence, esomeprazole has a superior bioavailability compared to omeprazole, reaching a value of 90% (the highest value among PPIs) with 40 mg/day [7, 63, 64].…”
Section: Pharmacology Of Esomeprazolementioning
confidence: 99%
See 1 more Smart Citation
“…A more favorable metabolism of esomeprazole leads to an increase in plasma AUC (esomeprazole, 20 mg/day, shows an AUC which is almost doubled compared to omeprazole at the same dosage) [62], which in turn corresponds to increased amounts of the drug reaching the pumps in the gastric parietal cells. Indeed, esomeprazole 20 mg/day exerts a superior intragastric pH control (pH ≥4) compared to the same dose of omeprazole at 8, 12, and 16 h in patients with GERD [59]. As a consequence, esomeprazole has a superior bioavailability compared to omeprazole, reaching a value of 90% (the highest value among PPIs) with 40 mg/day [7, 63, 64].…”
Section: Pharmacology Of Esomeprazolementioning
confidence: 99%
“…Based on current clinical evidence, which is partly sustained by the weight of numbers (see above), esomeprazole is the most efficacious antisecretory agent [59] for the treatment of GERD. As a consequence, not all PPIs are equal.…”
Section: Are Ppis All Equal?mentioning
confidence: 99%
“…Studies have already shown that oral esomeprazole 40 mg is the first PPI to provide greater intragastric acid control than all other PPIs [3, 4]. Furthermore, intravenous esomeprazole has previously been shown to provide a similar level of acid control to oral administration in healthy subjects when given as a 30-min intravenous infusion [11].…”
Section: Discussionmentioning
confidence: 99%
“…Esomeprazole is the first oral proton pump inhibitor (PPI) to provide a more profound and longer lasting inhibition of gastric acid secretion during a 24-hour period than all other PPIs [3, 4]. Clinical studies comparing esomeprazole with omeprazole and lansoprazole given in the doses recommended for the healing of erosive esophagitis show that oral esomeprazole demonstrates greater efficacy for the healing of erosive esophagitis and resolution of heartburn [5, 6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there was no difference between rabeprazole 20 mg and esomeprazole 40 mg with respect to effects on intragastric pH over the entire 24-hour period [51]. In one additional study that compared gastric acid control on day 5 following standard doses of esomeprazole (40 mg), rabeprazole (20 mg), lansoprazole (30 mg), pantoprazole (40 mg), and omeprazole (20 mg), esomeprazole maintained intragastric pH >4.0 for a mean of 14.0 h, while rabeprazole maintained intragastric pH >4 for 12.1 h. However, this study did not contain data on nocturnal acid control [52]. …”
Section: Introductionmentioning
confidence: 99%